2017
DOI: 10.3389/fpsyg.2017.01780
|View full text |Cite
|
Sign up to set email alerts
|

The Orienting Response in Healthy Aging: Novelty P3 Indicates No General Decline but Reduced Efficacy for Fast Stimulation Rates

Abstract: Automatic orienting to unexpected changes in the environment is a pre-requisite for adaptive behavior. One prominent mechanism of automatic attentional control is the Orienting Response (OR). Despite the fundamental significance of the OR in everyday life, only little is known about how the OR is affected by healthy aging. We tested this question in two age groups (19-38 and 55-72 years) and measured skin-conductance responses (SCRs) and event-related brain potentials (ERPs) to novels (i.e., short environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Hence, we posit that the locus of the age difference in distraction by unexpected sounds in visual oddball tasks may lie in the selective alteration of frontal networks underpinning the control of attention across sensory modalities. The proposition that the effect of aging unravels in relatively late stages of processing, after the initial detection of change, fits well with EEG findings indicating that aging does not modulate early markers of the orienting response in active tasks ( Berti et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…Hence, we posit that the locus of the age difference in distraction by unexpected sounds in visual oddball tasks may lie in the selective alteration of frontal networks underpinning the control of attention across sensory modalities. The proposition that the effect of aging unravels in relatively late stages of processing, after the initial detection of change, fits well with EEG findings indicating that aging does not modulate early markers of the orienting response in active tasks ( Berti et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…In oddball studies, a tendency towards a larger P3a has been observed in trials in which a SCR has been elicited (Lyytinen et al, 1992;Marinkovic et al, 2001) but other studies fail to link the SCR to any of the ERPs triggered by novel sounds (Barry et al, 2013;Rushby and Barry, 2009). In a recent auditory oddball study, large SCR to novel sounds were associated to large late-P3 amplitudes but no such association could be drawn with the early-P3 (Berti et al, 2017). Studies using drugs to modulate noradrenergic activity can also be useful to understand the links between the P3a and the LC-NE system.…”
mentioning
confidence: 97%
“…Finally, deviance distraction can also be modulated by other factors, such as participants’ age. For example, deviant sounds cause greater behavioural distraction in old age under certain conditions (Leiva, Andrés, & Parmentier, 2015; Leiva, Parmentier, & Andrés, 2015a) although this does not appear to reflect age-related differences in the electrophysiological orienting response (Berti, Vossel, & Gamer, 2017).…”
mentioning
confidence: 99%